2015
DOI: 10.1002/yea.3071
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the toxicity mechanism of octanoic and decanoic acids on Saccharomyces cerevisiae

Abstract: Octanoic (C8) and decanoic (C10) acids are produced in hypoxic conditions by the yeast Saccharomyces cerevisiae as by-products of its metabolism and are considered fermentation inhibitors in the presence of ethanol at acidic pH. This study aims to broaden our understanding of the physiological limits between toxicity and ester production in yeast cells. To this end, the non-inhibitory concentration (NIC) and maximum inhibitory concentration (MIC) values were first established for C8 and C10 at physiological pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 18 publications
3
42
0
Order By: Relevance
“…Regarding a putative impact on growth by toxic SCFAs3637, we were interested in clarifying whether a strong initial production of C 8 -FA accounts for the inhibition of further growth. Product spectra of selected strains were recorded after 12, 24 and 48 h; the latter constituting the regularly chosen measurement point.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding a putative impact on growth by toxic SCFAs3637, we were interested in clarifying whether a strong initial production of C 8 -FA accounts for the inhibition of further growth. Product spectra of selected strains were recorded after 12, 24 and 48 h; the latter constituting the regularly chosen measurement point.…”
Section: Resultsmentioning
confidence: 99%
“…All acids detected increased after fermentation. It was reported that yeasts are producers of octanoic and decanoic acids, which are by‐products of lipid synthesis during yeast fermentation (Borrull, López, Poblet, Cordero, & Rozès, ). This agrees with our results, from which octanoic acid increased significantly and decanoic acid was generated in the fermented tea.…”
Section: Resultsmentioning
confidence: 99%
“…That no effect was observed for decanoic acid is likely a consequence of the different mechanisms that yeast employs to overcome octanoic and decanoic acids stress. While decanoic acid penetrates the cell and is esterified, octanoic acid remains in the membrane (Borrull et al, ; Legras et al, ). Interestingly, there was no improvement in ethanol resistance and significant drops in cell growth were observed at 24 and 36 h; this contrasts with prior reports in the literature at lower oleic acid levels (Yazawa et al, ; You et al, ; Zheng et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In prior work, octanoic aid was shown to increase membrane permeability due to its retention in the cell membrane (Borrull et al, 2015). Liu et al (2013) used magnesium leakage as a measure of membrane permeability.…”
Section: Analysis Of Membrane Integritymentioning
confidence: 99%